HUBUNGAN KESEIMBANGAN DENGAN KEMAMPUAN TEKNIK SEPAK SILA DALAM EKSKUL PERMAINAN SEPAK TAKRAW DI SMAN 01 KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Khairul Azhar; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is error service that do not pass through the net, smash out the field, the bait is not good, the reception of the first ball more failed than the opponent's service, the lack of mastery of soccer techniques, less in acceptance of the first ball, body position often lose balance when feeding the ball. The purpose of this research is to find out whether there is a balance relationship with soccer technique skills in the game sepak takraw at student in extracurricular in SMAN 01 District rangsang District kepulauan meranti. The population in this student ekskul games sepak takraw which amounted to 12 people. A sampling technique was the overall population total sample, Instrument performed research is a balance test stork balance stand test which aims to measure the level of balance in a person performing movement.and test soccer skills capabilities aimed at knowing how much ability in performing soccer techniques from the sample used. After that, the data was analyzed to test for normality test at significant level a0,05 lilifors. Based on the research results, it can be concluded as follows.. Based on the results research, it can be concluded as follows. From the results obtained the balance there is a significant relationship to student is games sepak takraw in SMAN 01 District rangsang District kepulauan meranti where rhitung at significant level α (0,05) = , means rhitung (0.768)<rtabel (0.602)Key Words: Balance, Ability Of Technique Sila